The cuticle and plant defense to pathogens - Serrano, Mario; Coluccia, Fania; Torres, Martha; L’Haridon, Floriane; Métraux, Jean-Pierre (Frontiers in Plant Science, 2014)
The cuticle provides a physical barrier against water loss and protects against irradiation, xenobiotics and pathogens. Components of the cuticle are perceived by invading fungi and activate developmental processes during pathogenesis. In addition, cuticle alterations of various types induce a syndrome of reactions that often results in resistance to necrotrophs. This article reviews the current knowledge on the role of the cuticle in relation to the perception of pathogens and activation of defenses.